Developing a value-based pencak silat training model for life skills formation: A sport for development and peace perspective - Oman Hadiana; Iif Firmana; Nanan Abdul Manan; Irfan Fajrul Falah; Yani Fitriyani (Journal Sport Area)
Background: Pencak silat has now undergone a paradigm shift and training pattern. Internalization of morals and religious values is slowly disappearing. Now the focus of pencak silat training is oriented towards winning medals and financial awards. On the other hand, there has been a moral degradation of young people such as a lack of empathy and individualism. Research Objectives: The purpose of this study is to develop a tapak suci pencak silat training model in the perspective of Sport for Development and Peace based on value education towards life skills. Methods: The method used in this study is the ADDIE method (analysis, design, development, implementation, evaluation). The participants in this study were 56 athletes who were divided into two groups, namely the experimental group of 28 athletes and the control group of 28 athletes. In collecting data, researchers used several techniques, namely observation, questionnaires, and interviews. Findings/Results: The results indicate that the developed Pencak Silat training model has been tested valid, assessed by five theorists and five practitioners with a validity score of 0.99. The model was tested on a small scale and obtained a score of 76%, a medium scale test of 80%, and a field test of 81%, and was deemed practical. The effectiveness of the model was evident in the difference between the experimental group, with an average score of 146.36 and the control group, with 125.79. The experimental group was more effective in improving the life skills of Pencak Silat athletes. Conclusion: The conclusion of the study explains that the development of a pencak silat training model based on value education has provided an effective impact on athletes' life skills, especially in terms of emotional control, problem solving, leadership, and respect. Further research on the implementation of value education in other martial arts is very suitable in order to improve life skills.